ENHANCING CUSTOMER INSIGHT THROUGH ASPECT-BASED SENTIMENT ANALYSIS OF SMART DEVICE REVIEWS : CROSS-BRAND INSIGHTS FROM APPLE, SAMSUNG, AND XIAOMI - Al-Sabahi, Abdullah Yahya Moqbel; Fudholi, Dhomas Hatta (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
In today’s highly competitive smart device market, understanding customer sentiment is essential for driving product innovation and brand loyalty. This study applies Aspect-Based Sentiment Analysis (ABSA) using transformer-based models BERT, RoBERTa, and DistilBERT on over 20,000 reviews collected from Amazon, Flipkart, Walmart, and Best Buy between 2021 and 2024. The analysis focuses on customer feedback regarding Apple, Samsung, and Xiaomi smartphones and smartwatches. Key product aspects such as Battery, Camera, and Performance were extracted, and sentiment trends were compared by brand and device type. Findings reveal Samsung devices received the highest engagement, with its watches praised but phones criticized. Xiaomi’s reviews showed strong polarization, while Apple maintained consistent but lower review volumes. Temporal trends showed a significant rise in positive sentiment in 2024, indicating improving product satisfaction. This research offers actionable insights for original equipment manufacturers (OEMs) and marketers, highlighting which features drive satisfaction and how sentiment evolves over time.